PENERAPAN MODEL PEMBELAJARAN JEROLD E. KEMP DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS V MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 009 PARIT TERATAK AIR HITAM KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Mustaina Mustaina; Andrizal Andrizal; Sopiatun Nahwiyah (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2019)
This study aims to determine how the application of the Jerold learning model e. Kemp is able to increase students' interest in learning for fifth grade students of Islamic Religious Education at SD Negeri 009 Parat Teratak Air Hitam, Sntajo Raya District, Kuantan Singingi Regency. The subjects in this study were PAI teachers and fifth grade students, the object of the study was the Application of the Jerold E. Kemp Learning Model in Improving Student Interest in Class V Subjects of Islamic Religious Education. The population is 1 PAI teacher and student V SDN 009 Air Hitam Teratak Trench 21 (10 male and 11 female). The results of this study indicate the application of the Jerold learning model e. Kemp class V students of Islamic Education in State Elementary School 009 Parat Teratak Air Hitam Subdistrict Sntajo Raya Kuantan Singingi District were carried out well, this can be seen from the increase in each cycle, pre cycle 65.00%, cycle I increased to 100%, and second cycle is also 100%. And Application of Jerold E. Kemp Learning Model Can Increase Student Interest in Class V of Islamic Religious Education Subjects in SD9 009 Teratak Air Hitam Trench, Sentajo Raya Subdistrict, Kuantan Singingi District with a percentage increase in pre-cycle 65.00%, cycle I increased to 75, 00% and cycle II 95.00%.